2010
DOI: 10.1007/s11145-010-9262-y
|View full text |Cite
|
Sign up to set email alerts
|

Child writers’ construction and reconstruction of single sentences and construction of multi-sentence texts: contributions of syntax and transcription to translation

Abstract: Children in grades one to four completed two sentence construction tasks: (a) Write one complete sentence about a topic prompt (sentence integrity, Study 1); and (b) Integrate two sentences into one complete sentence without changing meaning (sentence combining, Study 2). Most, but not all, children in first through fourth grade could write just one sentence. The sentence integrity task was not correlated with sentence combining until fourth grade, when in multiple regression, sentence integrity explained uniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 41 publications
5
72
1
2
Order By: Relevance
“…In the opinion essay task, students generated ideas before writing and put them freely into sentences during text production. In the sentence-combining task, students were given a pre-determined set of sentences and had a narrow range of options to correctly combine them (Berninger et al, 2011;Strong, 1986). Spelling accuracy was assessed in the context of writing, in the opinion essays with and without planning Limpo & Alves, 2013a;Mackie & Dockrell, 2004;Nelson & van Meter, 2007;Wagner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the opinion essay task, students generated ideas before writing and put them freely into sentences during text production. In the sentence-combining task, students were given a pre-determined set of sentences and had a narrow range of options to correctly combine them (Berninger et al, 2011;Strong, 1986). Spelling accuracy was assessed in the context of writing, in the opinion essays with and without planning Limpo & Alves, 2013a;Mackie & Dockrell, 2004;Nelson & van Meter, 2007;Wagner et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, using structural equation modeling, Kim, Al Otaiba, Folsom, Gruelich, and Puranik (2014) found that spelling accuracy, but not handwriting fluency, was associated with syntactic complexity (see also Berninger et al, 2011). Greater spelling accuracy may allow writers to shift their linguistic concerns from single words to the organization of those words into larger units.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations